My First 100 Ocean Words - Ferrie, Chris; Dale-Scott, Lindsay, 1991- ([Naperville, Illinois] : Sourcebooks eXplore, an imprint of Sourcebooks Kids, 2020)
"A simple and colorful introduction to the first 100 ocean words every baby should know, from seaduck to seaweed, freighter to marina, and more!"--.
New Kid Book 2022 Spring.
Keywords: Oceanography -- Juvenile literature -- Terminology; Vocabulary -- Juvenile literature; Board books